The Challenge of Retiring in the Contemporary World - Fontoura, Daniele dos Santos (2014)
Retirement is experienced differently depending on the professional trajectories, on the ageing process and on personal characteristics. This article analyzes the testimonies of 70 subjects with ages above 45 that spoke about their perspectives and experiences regarding retirement. The results of the study point, on the one hand, towards the impact of retirement upon workers, challenging them to rethink and reorganize their lives. On the other hand, they show that there are different and diverging forms of dealing with retirement, influenced by the nature and conditions of work trajectories, as well as by the way people perceive and experience the ageing process.